TANAMAN KELOR SEBAGAI PELENGKAP PANGAN DAN NILAI EKONOMIS PADA MASYARAKAT DESA TISTA, KECAMATAN ABANG KABUPATEN KARANGASEM - I Made Suasti Puja (JURNAL SEWAKA BHAKTI, 2021)
The covid 19 pandemic has lasted almost 1 year 7 months from all over Indonesia, the most prominent in the economy is Bali island, because there are no foreign & domestic guests, that cause tourism sector. The economic contraction caused many people who work in that sector are lose their jobs and to survive they return to their home town to work as farmers. The covid-19 pandemic has not slowed yet the government to implement the Implementation of Community Activity Restrictions (PPKM). During the PPKM in Bali, the Universitas Hindu Indonesia (UNHI) have to carry out the Tri Dharma Perguruan Tinggi by carrying out the Community Service Program (KKN) the Thematic of the Universitas Hindu Indonesia with theme "Desa, Kala Tattwa: Ausadhining Bhumi". (glorify plants on earth with Desa, Kala, Tattwa). The students are given to choose which village for them to do KKN programe and continue to apply health protocols. The problem solving method, This community service is in the form of a facilitator who facilitates and motivates the implementation of empowerment in the community with the educational target of moringa plants as food and economic value to Mr. I Nyoman Sloka. Starts with the preparation stage, send a letter to the Head of Tista Village. Next, the students are explain the benefits of moringa plants and their economic value at Mr. I Nyoman Sloka's house and after approval, the students provided moringa plant seeds and planted Moringa trees together on existing land. Moringa can grow in the tropics and sub-tropical on all types of soil and resistant to drought with tolerance to drought up to 6 months. Moringa plants (Moringa oleifera) are also said to be the World's most value multipurpose trees and miracle trees. All parts of the Moringa plant have nutritional value, are efficacious for health and industrial benefits. The Tista Village community in Karangasem must always learn how to process Moringa plants so that they can be used as as various food products, various type of snacks, and medicine through various literacy and goverment trainings.